Hubungan Pemberian ASI Ekslusif dengan Kejadian Diare pada Bayi Usia 6-12 Bulan di Wilayah Kerja Puskesmas Tolamaera Kecamatan Gunungsitoi Idanoi Provinsi Sumatera Utara - Yesica Geovany Sianipar; Ratna Abigail Zebua; Friza Novita Sari Situmorang; Magdalena Br Barus; Rismalia Tarigan (Antigen : Jurnal Kesehatan Masyarakat dan Ilmu Gizi, 2024)
Early and exclusive breastfeeding is very important for a child's survival, and to protect them from various diseases to which they are susceptible and which can be fatal, such as diarrhea and pneumonia. The aim of this study was to determine the relationship between exclusive breastfeeding and the incidence of diarrhea in infants aged 6-12 months in the Tolamaera Community Health Center Working Area, Gunungsitoli Idanoi District, Gunungsitoli City, North Sumatra Province. This research is an analytical research using a cross sectional design, a sample of 75 people taken by total sampling. Analysis was carried out univariately and bivariately using the chi square test with a p- value <0.05. The results of this study show that there is a relationship between exclusive breastfeeding and the incidence of diarrhea in babies aged 6-12 months in the Tolamaera Community Health Center Working Area, Gunungsitoli Idanoi District, Gunungsitoli City, North Sumatra Province with a p value = 0.000. It is hoped that midwives in the Tolamaera Community Health Center Working Area, Gunungsitoli Idanoi District, Gunungsitoli City, North Sumatra Province, can provide education about exclusive breastfeeding to the community, especially to mothers of babies and for mothers. It is hoped that they will try to provide exclusive breastfeeding to babies up to 6 months old.